Communauté de pratique dans le domaine de la promotion de la santé : analyse du sentiment d’appartenance et des pratiques de leadership - Lise Renaud; Monique Caron-Bouchard; Julia Gaudreault-Perron; Hélène Gayraud (Communiquer)
Setting up a community of practice makes it possible to investigate the interactive dynamics of the group and its relation to leadership. What are the conditions for setting up and maintaining a community of practice? What circumstances enhance the cohesion of the group? The community studied concerns a partnership between members of the public and private sectors whose goal is to offer health promotion interventions intended for elementary schools. Various research tools, quantitative and qualitative, were used: the logbook, the questionnaire of profile, interviews (n=15) as well as postings (n=147) on a platform. Findings from this study indicate that this community of practice is centered not on problem-solving or training but rather on sharing of experiences and resources. The interest in studying this community of practice, its vitality and its mechanisms, rests upon good group facilitation and the sense of belonging of participants. When leadership is not shared by its members and is exerted mainly by the initiator of the community, the vitality of the community of practice is compromised, and even seriously undermined.